Response to TMS treatment for depression associated with higher levels of psychological well-being. (June 2022) - Toth, Catherine; King Johnson, Marcie L.; Heinzerling, Amanda; Trapp, Nicholas
Abstract: Treatment resistant depression (TRD) is a complex condition associated with a great deal of disability and suffering. The relationship between TRD and psychological well-being (PWB) appears to be more complex than a simple antithesis. Transcranial magnetic stimulation (TMS) is a well-tolerated treatment for TRD. However successful, a drawback for TMS is that it has a lack of predictive biomarkers for treatment response. Our study focuses on the relationship between PWB and treatment resistant depression, and how PWB relates to TMS treatment response. We hypothesized that TMS treatment responders would have higher levels of PWB at baseline. In this study of 21 patients with TRD, we used the Ryff Scales of Psychological Well-Being and Patient Health Questionnaire-9 (PHQ-9). We found a significant relationship between environmental mastery, purpose in life, self-acceptance, and total PWB with baseline depression but no significant correlation between autonomy, personal growth, and positive relations with others and baseline PHQ-9 scores. No Ryff domain of PWB significantly predicted change in PHQ-9 score. Interestingly, however, we found that TMS responders had higher levels of autonomy (M(SD) = 62.10(10.46), p = 0.022) and personal growth (M(SD) = 65.00(11.04), p = 0.007) than non-responders at baseline. These specific aspects of well-being appear to be distinct from depression and particularly important in treatment response. This discovery suggests that assessing PWB might prove clinically useful when assessing future candidates for TMS treatment of TRD. Further research is necessary to evaluate the effects of TMS on PWB since these may be distinct from its effect on depression symptomology.